2016
DOI: 10.1136/ejhpharm-2016-000931
|View full text |Cite
|
Sign up to set email alerts
|

A stability study of amphotericin B, colistin and tobramycin in a hydrophilic suspension commonly used for selective decontamination of the digestive tract by HPLC and in vitro potency measurements

Abstract: ObjectivesA suspension for oral use which consists of three non-absorbable antibiotics (amphotericin B, colistin and tobramycin) is often used in clinical practice for the selective decontamination of the digestive tract (SDD) of patients in intensive care. Such a therapy is a preventive tool to minimise the risk of pneumonia and bacteraemia in intubated patients. The administration and the treatment results are controversially discussed. One limiting factor for a unique SDD treatment in the hospitals is a lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…and Li et al noted no significant change in concentration after 60 days at 4 °C [ 25 ]. Similarly, Pfeifer et al reported no degradation for at least six months at 2–8 °C, although instability was observed at 25 °C [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…and Li et al noted no significant change in concentration after 60 days at 4 °C [ 25 ]. Similarly, Pfeifer et al reported no degradation for at least six months at 2–8 °C, although instability was observed at 25 °C [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SDD medication was prepared by our clinic pharmacy with a stability-approved protocol according to the pattern used in SELECT trial expanded by vancomycin [ 11 , 12 ]. A combination of colistin base (100 mg), tobramycin base (80 mg), and amphotericin B (500 mg) and vancomycin (125 mg) was applied separately (10 ml each) due to stability concerns adding vancomycin to the formulation.…”
Section: Methodsmentioning
confidence: 99%
“…Sowohl der postoperative als auch der gesamte Intensivaufenthalt war in der RAMIE-Gruppe im Median 2 Tage kürzer (p < 0,001); nur die Wiederaufnahmerate auf eine Intensivstation unterschied sich nicht signifikant (16,0 % vs. 26,7 %, p = 0,081). Die mediane Krankenhausverweildauer betrug nach RAMIE nur 14 Tage (IQR [12][13][14][15][16][17][18][19][20][21][22], verglichen mit 20 Tagen (IQR 14-37, p < 0,001) in der Kontrollgruppe.…”
Section: Morbidität Und Mortalitätunclassified